2009
DOI: 10.4049/jimmunol.0900298
|View full text |Cite
|
Sign up to set email alerts
|

CXCR2 Is Required for Neutrophilic Airway Inflammation and Hyperresponsiveness in a Mouse Model of Human Rhinovirus Infection

Abstract: Human rhinovirus (RV) infection is responsible for the majority of virus-induced asthma exacerbations. Using a mouse model of human RV infection, we sought to determine the requirement of CXCR2, the receptor for ELR-positive CXC chemokines, for RV-induced airway neutrophilia and hyperresponsiveness. Wild-type and CXCR2−/− mice were inoculated intranasally with RV1B or sham HeLa cell supernatant. Following RV1B infection, CXCR2−/− mice showed reduced airway and lung neutrophils and cholinergic responsiveness co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 48 publications
5
71
1
Order By: Relevance
“…Our analysis revealed that both chemokines are necessary for a normal neutrophil response, as in their absence, neutrophil recruitment to the wound was severely impaired. These findings are in agreement with the reduced neutrophil recruitment observed in inflammation in knockout mice for CXCR1, CXCR2, or CXCL1 (one of the mouse CXCL8 functional homologs) (40)(41)(42)(43)(44). Furthermore the mRNA levels of key proinflammatory mediators, such as IL-1b and PTGS2b, were affected in both morphants, strongly suggesting that in the absence of either Cxcl8, zebrafish acute inflammation is significantly attenuated.…”
Section: Discussionsupporting
confidence: 78%
“…Our analysis revealed that both chemokines are necessary for a normal neutrophil response, as in their absence, neutrophil recruitment to the wound was severely impaired. These findings are in agreement with the reduced neutrophil recruitment observed in inflammation in knockout mice for CXCR1, CXCR2, or CXCL1 (one of the mouse CXCL8 functional homologs) (40)(41)(42)(43)(44). Furthermore the mRNA levels of key proinflammatory mediators, such as IL-1b and PTGS2b, were affected in both morphants, strongly suggesting that in the absence of either Cxcl8, zebrafish acute inflammation is significantly attenuated.…”
Section: Discussionsupporting
confidence: 78%
“…These data additionally emphasize the relevance of mechanisms that may be involved in the initiation and progression of complex pathologies such as anaphylaxis and tumorigenesis [23,56,57,59]. Although our studies are by no means exhaustive, the combined data from AKNA KO and KO2 mice concur with our hypothesis that AKNA has a regulatory function on gene transcription networks, which we suggest is linked to the mechanisms that control the degree of neutrophil responses to pathogen invasion ( Figure 8D).…”
Section: Discussionsupporting
confidence: 78%
“…Hence, in the context of a linkage with strain in mice and potentially with race in humans, we consider two hypothetical scenarios in AKNA deficiency: (1) acute and fatal hyper-reactions in genetically prone populations [56,57] and (2) subtle states of inflammation in populations with no inherent genetic susceptibility that create a microenvironment that facilitates the initiation and progression of degenerative and/or neoplastic disorders [58].…”
Section: Discussionmentioning
confidence: 99%
“…In the CS-only and O 2 1CS mice, we found increased numbers of inflammatory cells in the BALF and increased expression of CXCR2/IL8Ra lung mRNA, suggesting a correlation between chronic CS exposure and increased lung inflammation. Induction of CXCR2/IL8Ra has previously been demonstrated in animal models of CSinduced COPD, Streptococcus pneumoniae, and rhinovirusinduced airway inflammation (30)(31)(32)(33). We did not find an association between early postnatal hyperoxia exposure and increased inflammation in the adult lung.…”
Section: Discussioncontrasting
confidence: 36%